PENGARUH KEMUDAHAN, KEAMANAN, KETANGGAPAN, HARGA DAN REPUTASI PERUSAHAAN TERHADAP KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN PRODUK KERAJINAN DANBO SECARA ONLINE - Randika Fandiyanto; Raden Andi Sularso; Bambang Irawan (Relawan Jurnal Indonesia, 2017)
The high business competition is currently pushing many industries of Micro and Small Medium Enterprises to continue to innovate both the attributes of products and marketing, currently pushed UMKM to enter the online business through e-commerce into a promising opportunity in the chain selanjuanua network. This study aims to describe the ease, security, responsiveness, price, reputation, trust and decision of Danbo handicraft sales at Trebungan Handicraft House, Situbondo Regency, beside that this research is also explanatory research which analyze each exogenous variable to variable Endogenous This research was conducted in Situbondo Regency precisely through Trebungan Home Industry, with 634 people and technique of sampling using proportional random sampling